A secured transmission model for EPC network. (2015) - Li, Zhongwen; Li, Qian; Xu, Zhibin; Jiang, Hai; Li, Kuan-Ching
Electronic product code (EPC) network is an advanced and integrated complex system, with the ultimate goal of building an internet of physical objects, and therefore, appropriate security schemes ensuring its resilience to sophisticated attacks, data confidentiality, client privacy protection and other features ought to be re-designed and implemented. For such, this paper proposes a new transmission model of EPC network, which includes an effective multi-key generation centre (KGC) scheme and secure protocols in the ONS query system. Compared to traditional models based on certificate, the proposed model has obvious advantages, such as easy implementation and avoidance of complex certificate management. Based on certificateless public key cryptography (CL-PKC), multi-ONS query process is designed to meet the security requirement of EPC network with decentralised root ONS administration and object information transmission in this model. Analysis shows that the new transmission model of EPC network has new properties as improvement, such as anonymity, tolerance, security and DDoS attack-resistance.